ETpathfinder: a cryogenic testbed for interferometric gravitational-wave detectors. (26th September 2022) - Utina, A; Amato, A; Arends, J; Arina, C; de Baar, M; Baars, M; Baer, P; van Bakel, N; Beaumont, W; Bertolini, A; van Beuzekom, M; Biersteker, S; et al.
Abstract: The third-generation (3G) of gravitational wave observatories, such as the Einstein Telescope (ET) and Cosmic Explorer, aim for an improvement in sensitivity of at least a factor of ten over a wide frequency range compared to the current advanced detectors. In order to inform the design of the 3G detectors and to develop and qualify their subsystems, dedicated test facilities are required. ETpathfinder prototype uses full interferometer configurations and aims to provide a high sensitivity facility in a similar environment as ET. Along with the interferometry at 1550 nm and silicon test masses, ETpathfinder will focus on cryogenic technologies, lasers and optics at 2090 nm and advanced quantum-noise reduction schemes. This paper analyses the underpinning noise contributions and combines them into full noise budgets of the two initially targeted configurations: (1) operating with 1550 nm laser light and at a temperature of 18 K and (2) operating at 2090 nm wavelength and a temperature of 123 K.